Risiko Fotoreaktivasi terhadap Kualitas Mikrobiologi Air Minum Isi Ulang - Yushananta, Prayudhy; Ahyanti, Mei (Politeknik Kesehatan Tanjungkarang, 2017)
Photoreactivation is a direct process of repairing a damaged DNA with the help of ultraviolet in the range of 320-370 nm. Research is designed to acknowledge the effect of time exposure and UV vis ray’s intensity to numbers of Coliforms and E.coli. The results prove the effect of UV exposure time on the increase of coliform which is 60,2% (p-value=0,0001). The increase of coliform happens after 180th minutes of exposure. But, in this research there is no effect of UV’s intensity towards both numbers of coliform (p-value = 0,152) and E.Coli (p-value=0,578). Besides buying a refilled mineral water from a water depot whose disinfecting with UV ray and ozone combined, closing the gallon of mineral water since the first day being used to avoid being exposed by UV vis ray from the sun is a must-do to avoid photoreactivation process.